Afterword to Marko the Damned - Krys, Svitlana; Storozhenko, Oleksa (My University, 2024)
In the haunting and gothic landscape of 1640s Ukraine, Marko the Damned (1879) by Oleksa Storozhenko weaves a chilling tale of rebellion, betrayal, and the supernatural. Set against the backdrop of the kozak struggle for freedom, this gripping novel follows the harrowing journey of Marko, a kozak warrior ensnared by dark forces. As the kozaky rise up against their oppressors, Marko finds himself torn between loyalty to his comrades and a cursed destiny that threatens to consume him. With every step, he battles both the homeland’s enemies and the sinister powers that seek to claim his soul. Storozhenko’s masterful storytelling plunges readers into a world of eerie shadows and moral dilemmas, where the fight for freedom intertwines with a descent into the macabre. Marko the Damned is a captivating exploration of human resilience and the unyielding spirit of the kozaky, destined to leave readers both enthralled and unsettled.
Keywords: adults; classics; gothic & horror; historical fiction; tales & legends